Do ódio virtual à violência real: uma análise da relação entre o cyberbullying e os massacres escolares - Barbosa, Naomi André Cambará (2025)
The school plays a fundamental role in the holistic development of individuals, not only in terms of knowledge building and the broadening of their worldview, but also as a space of experiences that shape their social and emotional development. Among the various functions assumed by the school institution, its relevance stands out as an environment of social interactions in which individuals establish relationships and develop skills such as coexistence, empathy, and cooperation. However, these interactions can also reflect dynamics of inclusion and exclusion, processes intrinsic to school life. Phenomena such as bullying highlight how exclusion can deeply affect students’ lives, generating consequences that extend beyond the limits of the school. With the advent and popularization of new technologies, these social dynamics have acquired a new dimension. Interactions and conflicts, previously restricted to the physical school space, now extend to social networks and digital platforms, potentially taking on even larger and more complex proportions. Many of these episodes, often premeditated and announced either subtly or explicitly on digital platforms, raise urgent questions about the relationship between the school environment, social interactions, and the use of social networks. Given the above, it is observed that the processes of bullying and cyberbullying are interconnected with school massacres. Likewise, it is possible to analyze, based on the statements and experiences of students and teaching staff, how hate speech can influence and reshape the school environment and its spatialities. The data collected through questionnaires applied to students and teachers reveal vulnerabilities and the growing presence of hate speech and motivating content in virtual social networks. Bullying and cyberbullying, therefore, do not result from a single factor but from multiple dimensions. Although bullying is not the only determinant, it appears as a recurring element in attack narratives. The study concludes that violence is fluid, reinvents itself, and finds in cyberspace both an environment of support and a means of spreading hostility.